ChemInform Abstract: Stereodivergent Hydrogermylations of α‐Trifluoromethylated Alkynes and Their Applications in Cross‐Coupling Reactions. Issue 33 (August 2015) - Schweizer, Stephane; Tresse, Cedric; Bisseret, Philippe; Lalevee, Jacques; Evano, Gwilherm; Blanchard, Nicolas
Abstract (Z)‐ and (E)‐α‐CF3‐vinylgermanes are regio‐ and stereoselectively prepared under radical or Pd‐catalyzed conditions.